2007
DOI: 10.3892/or.18.6.1521
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines and oxidative stress/antioxidant parameters characterize the bio-humoral profile of early cachexia in lung cancer patients

Abstract: Cancer-related cachexia, that is present in about 50% of cancer patients and accounts for 20% of all cancer deaths, is clinically characterized by progressive weight loss, anorexia, metabolic alterations, asthenia, depletion of lipid stores and severe loss of skeletal muscle proteins. The main biochemical and molecular alterations that are responsible for the syndrome are prematurely present in the progress of the disease and the identification of the early stages of cachexia can be useful in targetting patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…Taken together, these data suggest that oxidative stress might be an important inducer of MIC-1 production. The presence of increased oxidative stress (18)(19)(20) could potentially explain why both cachectic and obese patients display increased MIC-1 levels. We suggest that both extreme cachexia in cancer patients and morbid obesity may result in nutritional stress and subsequently oxidative stress in adipocytes and other tissues which may in turn stimulate MIC-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that oxidative stress might be an important inducer of MIC-1 production. The presence of increased oxidative stress (18)(19)(20) could potentially explain why both cachectic and obese patients display increased MIC-1 levels. We suggest that both extreme cachexia in cancer patients and morbid obesity may result in nutritional stress and subsequently oxidative stress in adipocytes and other tissues which may in turn stimulate MIC-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in some of the proteins participating in this synergy -such as mitofusin -have been described in experimental cancer cachexia [21]. Cytokines, TNF-a, in particular, are associated with increased oxidative stress in skeletal muscle during cancer [22]. Padrao et al [23], using a bladder cancer rat model of muscle wasting, concluded that mitochondrial dysfunction was associated with an accumulation of oxidized and nitrated proteins not repairable by mitochondrial proteases and the mitochondrial shaping machinery [24 ] (Figure 1).…”
Section: Oxidative Damage and Mitochondrial Dysfunctionmentioning
confidence: 98%
“…Mol Cell Endocrinol 2013, 379: [19][20][21][22][23][24][25][26][27][28][29]. The focus of this review was to discuss promising human physiological systems underpinning the decline of mitochondrial and skeletal muscle health with advancing age while highlighting therapeutic strategies such as aerobic exercise and caloric restriction for combating age-related functional impairments.…”
mentioning
confidence: 99%
“…The utilization of NEFAs in the liver is attenuated [2], mainly due to decreased expression levels and activities of carnitine palmitoyltransferases I and II (CPT I and CPT II) which accelerate fatty acid β-oxidation [3,4]. Additionally, some pro-inflammatory factors such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and interferon-γ (IFN-γ) inhibit the lipoprotein lipase, thus preventing adipocytes from storing fatty acids [5]. …”
Section: Introductionmentioning
confidence: 99%